Russian about Development Assistance : Findings of Public Opinion Research - Nationwide Representative Survey - Leveda Center (World Bank, Washington, DC, 2017)
Public opinion research of the Russian population attitudes towards Official Development Assistance(ODA) was undertaken in 2010 as part of the DFID supported WB Russia as a Donor Initiative (RDI) program assisting Russian Government in its development aid efforts. The research was conducted by Levada-Center, an independent polling and sociological company, using qualitative (in-depth interviews with opinion leaders) and quantitative (nationally representative survey) methodology. Volumes 1 and 2 report respectively on the findings of the qualitative and quantitative surveys. The qualitative survey included 25 opinion leaders interviews (public officials, NGOs, academia, business community, and the media), conducted in the cities of Moscow, St. Petersburg, Krasnoyarsk, and Rostov. The interviews covered economic situation in Russia; Russia's global role; potential recipient countries of Russian ODA and types of assistance; and overall awareness of Russian ODA activities. The opinion leaders share a common feeling that Russia is a "rich country with poor people" that still should take increasingly active role in development aid, being an influential "world power". Opinion leaders believe that Russian ODA should focus on: (i) countries affected by natural disasters; (ii) neighboring former Soviet bloc countries that have traditionally been "a zone of Russia's historic responsibility"; and (iii) countries posing global security threats. "Giving a fishing rod, not fish" was indicated as a preferred approach to development aid. Joint ODA programs with the World Bank and other multilateral organizations were supported as a tool to strengthen Russia's donor role, learn international practices, and reduce corruption risks. Most of the interviewees had little knowledge of the Russian ODA, but they thought it was matching the national interests, and were interested to learn more on ODA. A need to inform the general public about Russia's donor role was highlighted. The nationwide survey included 1503 respondents from 96 cities and 35 rural settlements located in 44 regions of Russia. The sample was nationally representative of the Russian adult population (aged 18 years and older). The survey showed that 3/4 of the population approve Russia's development aid to the poorest countries with preferred areas of Russia support being countries affected by natural disasters (64 percent support) and poor CIS countries (22 percent). Potential assistance could be provided in a form of sending Russian specialists to work in developing countries (58 percent); educating their students in Russia (51 percent); and supplying food and equipment at subsidized prices (30 percent). Medical care, access to basic education, and developing industrial facilities and infrastructure are seen as the areas of most effective assistance. Russia ODA collaboration with multilateral organizations is also seen favourably. Motivation of Russia ODA in the views of the respondents included: (i) shared moral responsibility for reduction of extreme poverty in developing countries; (ii) expansion of the circle of countries friendly to Russia; (iii) reduction the threat of terrorism and drug traffic between Russia and neighboring countries; and (iv) increase of Russia's influence and prestige in the world.